2015
DOI: 10.3342/ceo.2015.8.1.46
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Emergence Agitation in Adults Undergoing General Anesthesia for Nasal Surgery

Abstract: ObjectivesTo identify the incidence and the risk factors of emergence agitation in adults undergoing general anesthesia for nasal surgery.MethodsWe retrospectively examined 792 patients aged ≥18 years who underwent general anesthesia for elective nasal surgery between July 2012 and August 2013. Patients in the postanesthesia care unit with a Richmond Agitation Sedation Scale≥+1 at any time were considered to have emergence agitation.ResultsThe overall incidence of emergence agitation is 22.2%. From multivariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
157
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(167 citation statements)
references
References 18 publications
7
157
2
1
Order By: Relevance
“…The fi rst assessment of postoperative (also referred to as interval) delirium was done around 24 h after surgery; 20 we selected the timing of the fi rst assessment to avoid diagnosing emergence delirium that can occur immediately after general anaesthesia and is not associated with adverse outcomes. 21,22 Twice daily (in the morning from 0800 h to 1000 h and in the evening from 1800 h to 2000 h) until the seventh day after surgery, we assessed delirium by the Confusion Assessment Method for the ICU (CAM-ICU); (appendix), 23 which has been validated in Chinese patients in the ICU setting 24 and the feasibility of which had been established in our other studies. 25,26 CAM-ICU addresses the four features of delirium, namely, acute onset of mental status changes or a fl uctuating course, inattention, disorganised thinking, and altered level of consciousness.…”
Section: Discussionmentioning
confidence: 99%
“…The fi rst assessment of postoperative (also referred to as interval) delirium was done around 24 h after surgery; 20 we selected the timing of the fi rst assessment to avoid diagnosing emergence delirium that can occur immediately after general anaesthesia and is not associated with adverse outcomes. 21,22 Twice daily (in the morning from 0800 h to 1000 h and in the evening from 1800 h to 2000 h) until the seventh day after surgery, we assessed delirium by the Confusion Assessment Method for the ICU (CAM-ICU); (appendix), 23 which has been validated in Chinese patients in the ICU setting 24 and the feasibility of which had been established in our other studies. 25,26 CAM-ICU addresses the four features of delirium, namely, acute onset of mental status changes or a fl uctuating course, inattention, disorganised thinking, and altered level of consciousness.…”
Section: Discussionmentioning
confidence: 99%
“…3 Depending on the patient population and methods used to diagnose ED, previous studies have reported incidences varying from 4.7 to 22.2% in the adult population. [4][5][6][7][8][9] Only one other study 5 has described the clinical consequences of this potentially harmful state, which involved catheter removal, attempts at self-extubation and injuries to the patients as well as the staff.…”
mentioning
confidence: 99%
“…Male gender, type of surgery, inhalation anaesthetics, presence of tracheal tube and preoperative benzodiazepine medication are risk factors for postoperative agitation in adults. Emergence agitation is especially common after ENT surgery, where 55.4% of patients experienced agitation 11 . High incidence of emergence agitation after ENT surgery may be attributable to a sense of suffocation.…”
Section: Discussionmentioning
confidence: 99%
“…The patient received IV midazolam (0.04 mg/kg) 5 minutes prior to induction. 11,12 Prior to induction Inj. glycopyrrolate 0.2 mg was given.…”
Section: Limitations Of the Studymentioning
confidence: 99%